Health insurance in Myanmar: The views and perception of healthcare consumers and health system nformants on the establishment of a nationwide health insurance system - Marjolein van Rooijen; Chaw-Yin Myint; Milena Pavlova; Wim Groot (Risks, 2018)
(1) Background: Health insurance and social protection in Myanmar are negligible, which leaves many citizens at risk of financial hardship in case of a serious illness. The aim of this study is to explore the views of healthcare consumers and compare them to the views of key informants on the design and implementation of a nationwide health insurance system in Myanmar. (2) Method: Data were collected through nine focus group discussions with healthcare consumers and six semi-structured interviews with key health system informants. (3) Results: The consumers supported a mandatory basic health insurance and voluntary supplementary health insurance. Tax-based funding was suggested as an option that can help to enhance healthcare utilization among the poor and vulnerable groups. However, a fully tax-based funding was perceived to have limited chances of success given the low level of government resources available. Community-based insurance, where community members pool money in a healthcare fund, was seen as more appropriate for the rural areas. (4) Conclusion: This study suggests a healthcare financing mechanism based on a mixed insurance model for the creation of nationwide health insurance. Further inquiry into the feasibility of the vital aspects of the nationwide health insurance is needed.
Keywords: 330; basic health insurance; voluntary supplementary health insurance; tax-based funding; community-based insurance; Myanmar